BONA, C. (2021). Humanizar la educación. Barcelona: Plaza Janes, 225 paginas, ISBN 978-84-01-02231-9 - Tirso Valcárcel-Resalt Castillo (Universidad de La Rioja, 2021)
BONA, C. (2021). Humanizar la educación. Barcelona: Plaza Janes, 225 paginas, ISBN 978-84-01-02231-9.